Complex Pyogenic Liver Abscess: Outcome of Open vs Laparoscopic Drainage - Rashid Aslam; Farrukh Ozair Shah; Muhammad Nadir Shah; Mehtab Abdullah (Gandhara University, 2023)
OBJECTIVES Our study aimed to evaluate the safety and efficacy of laparoscopic drainage as a management of complex pyogenic liver abscesses in comparison to open surgical drainage. METHODOLOGY The comparative research design was used to compare the outcomes, complications, perioperative morbidity, mortality, and potential recurrence of 60 patients with a complex pyogenic liver abscess who were hospitalized at the General Surgery Department of Hayatabad Medical Complex Peshawar and treated either laparoscopically or openly from January 2019 to December 2020. 30 patients had open drainage management, while 30 patients received laparoscopic drainage management. For all patients, pus was examined for culture sensitivity. Patients with a small, solitary and unilocular pyogenic liver abscess that improved with antibiotic therapy and or/and percutaneous drainage were excluded. Each patient had a thorough clinical evaluation, lab tests, ultrasound, computed tomography, or magnetic resonance imaging of the pelvis and abdomen. RESULTS All patients underwent abdominal ultrasonography & sonographic diagnosis was made in 43(71.7%), followed by a computed tomography scan (CT) in 12(20%) & magnetic resonance imaging (MRI) diagnosis was made in 5(8.3%) patients respectively. Diabetes mellitus was present in 15(25%) patients, severe chronic obstructive pulmonary disease in 10(16.7%) and severe anemia in 9(15%) patients. All individuals associated with co-morbidity were considered high-risk patients. CONCLUSION Laparoscopic drainage of liver abscess has a shorter surgical time, lower morbidity rate, and shorter hospital stay as compared to open surgical drainage.